Prevalence, Pattern and Determinants of Substance Abuse Among Adolescents in Bagalkot, Karnataka, India - Bhagavati, Sushmita; Natekar, Deelip; Dhandargi, Utalbasha (National Journal of Community Medicine, 2023)
Background: Adolescence is the age of curiosity, experimentation and new roles. This is the age children start to explore the world and test everything around them. Substance abuse is an alarming problem among adolescents in India. The objective is to assess the prevalence, pattern and determinants of substance abuse among adolescents of Bagalkot. Methods: A cross sectional study with a sample of 384 adolescents, selected by disproportional stratified random sampling. WHO ASSIST was used to assess the prevalence and pattern of substance abuse. The data was entered in MS excel sheet and transferred to SPSS 18 for analysis. Results: the mean age of the sample was 16.4 ± 2.44 years. 71.9% were males and 28% were females. Among 384 adolescents 20.3% used to consume tobacco and 21.4% consumed alcohol, 2.6% consumed cannabis, 15.6% had consumed inhalants. Among Tobacco users 53.85% were 18 to19 years of age. Conclusion: The overall substance abuse among adolescents is about 21%. Age, Gender, and Peer pressure, increase the risk of substance abuse. The substance abuse prohibitor strategies must be strengthened to reduce the prevalence of substance abuse among adolescents.